Pharmacokinetic Properties of Nintedanib in Healthy Volunteers and Patients With Advanced Cancer. (6th October 2016) - Dallinger, Claudia; Trommeshauser, Dirk; Marzin, Kristell; Liesener, Andre; Kaiser, Rolf; Stopfer, Peter
Abstract: Nintedanib, a triple angiokinase inhibitor, has undergone clinical investigation for the treatment of solid tumors and idiopathic pulmonary fibrosis. Nintedanib (Vargatef ® ) plus docetaxel is approved in the EU for the treatment of patients with adenocarcinoma non‐small cell lung cancer (NSCLC) after first‐line chemotherapy, and as monotherapy (Ofev ® ) in the United States and EU for the treatment of patients with idiopathic pulmonary fibrosis. Pharmacokinetics (PK) of nintedanib after oral single and multiple doses and intravenous (IV) administration were assessed using 3 data sets: (1) an absolute bioavailability trial that enrolled 30 healthy volunteers; (2) a pooled data analysis of 4 studies that enrolled a total of 107 healthy volunteers; and (3) a pooled data analysis of 4 studies that enrolled a total of 149 patients with advanced cancer. In the absolute bioavailability trial of healthy volunteers, nintedanib showed a high total clearance (geometric mean 1390 mL/min) and a high volume of distribution at steady state (Vss = 1050 L). Urinary excretion of IV nintedanib was about 1% of dose; renal clearance was about 20 mL/min and therefore negligible. There was no deviation from dose proportionality after IV administration in the dose range tested. Absolute bioavailability of oral nintedanib (100 mg capsule) relative to IV dosing (4‐hour infusion, 6 mg) was slightly below 5%. Nintedanib was quickly absorbed after oral administration. It underwent rapid and extensive first‐pass metabolism and followed at least biphasic disposition kinetics. In advanced cancer patients, steady state was reached at the latest at 7 days for twice‐daily dosing. Nintedanib's PK was time‐independent; accumulation after repeated administration was negligible.